Avaliação de cuidadores de pacientes em cuidados paliativos na atenção domiciliar - COSTA, Raylena Martins da (2022)
Improving the quality of life of patients and families facing a life-threatening disease is one of the pillars of the care modality called palliative care. A multidisciplinary team minimizes the effects of the disease through prevention, relief from pain and suffering, in addition to others physical, social, psychological and spiritual symptoms. This care is indicated even at the beginning of the diagnosis because these illnesses involve a multidimensional situation that affects the life of the patient and the main caregiver, who, in most cases, is a family member. the ability to care for the family member of patients undergoing palliation in home care. This is a cross-sectional quantitative study that addresses aspects related to the ability to care for these family members and sociodemographic characteristics. The research was carried out in the city of São Luís/MA, with relatives of patients assisted by the home care service of the Melhor em Casa Program with centers located in hospitals in the municipal health network. Data collection consisted of surveying information on sociodemographic characteristics and the ability to remotely care for the relative responsible for the patient for a period of four months. The Ability to Care in Palliatives-ECCP Scale was applied to the family member by telephone, in an adapted way. The results indicated that the caregivers of patients at home were female (91.1%), brown (62.5%), single (50%), complete high school (53%), unpaid domestic workers (31, 3%), family income between 1 and 2 minimum wages with an average of 1.9; age group between 22-76 with an average of 46.6 years, own house (87.5%), number of residents in the household ranged from 2 to 10 with an average of 4 cohabitants. They had good ability to care for practical issues of this act, evidenced by the highest score ≥ 21, but with vulnerabilities related to emotional dimensions with a more evident score of 26-35 and relational/self-care with a more significant score ≤ 25, according to the ECCP scale. The scores demonstrate the need for professional intervention in the last two dimensions to improve the act of caring, reflecting on the overall well-being of the family member and patient registered in the program.